Iowaite in serpentinite muds at Sites 778, 779, 780, and 784: a possible cause for the low chlorinity of pore waters - Heling, Dietrich; Schwarz, Alexander (ODP proceedings. Scientific results, 1992)
The <63-µm fractions of serpentinite muds from two seamounts on the Mariana and Izu-Bonin forearcs were analyzed for mineral composition byX-ray diffraction and forchemical composition byX-ray fluorescence. The silt fraction of the muds consists predominantly of chrysotile, brucite, and ample amorphous constituents. Chlorite and smectite are less abundant components.